The Pension Fund of Ukraine and Improvement of Pension Provision - Bulygina Anastasiia V. (Bìznes Inform, 2020)
Beginning of reforming the system of pension provision in Ukraine started over 15 years ago, but now there are many questions and problems related to the improvement of the Ukrainian system of pension provision. The article is aimed at studying the issues related to the problems and ways of improving the system of pension provision in Ukraine. The current status of Ukrainian pension provision is examined. Advantages and disadvantages of the solidarity system are determined. The inefficiency of using the first pillar of the pension system only is substantiated. Attention is emphasized on the modern system of pension provision to identify a number of problems: increasing the retirement age; deficit of budget funds; complex demographic situation that is reflected in the imbalance between the working population and pensioners; shadow payments to employees etc. Negative consequences of the Ukrainian tendency of aging of the population are defined. The main economic indicators of pension system, such as level of pension payments, wages, coefficient of substitution of these indicators etc. are analyzed. Statistics are analyzed and the dynamics of economic indicators characterizing the status of the Ukrainian pension system during 2017–2019 are outlined. Statistical data on revenues and expenditures of the pension fund of Ukraine is considered. The main problems of Ukrainian pension provision are identified. The necessity and feasibility of development of the accumulation pension system and the system of non-State pension provision are substantiated. The ways to improve pension provision in Ukraine are determined.